PENGARUH REKRUTMEN, SELEKSI, DAN PELATIHAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT SHF - Nerissa Arviana; R Wasisto Ruswidiono (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study was to examine the effect of recruitment, selection, and training on the work productivity of PT SHF employees. Based on the results of a meeting with HRD PT SHF, it was found that employee work productivity in January-April 2022 was at a mid level and there was a research gap that examined recruitment, selection, training on employee productivity. The research form of this research using descriptive and causality research. An amount of population in this study/research were 70 employees of PT SHF and used a sample of 55 respondents using purposive sampling technique. From the results of the questionnaire given by the respondents, measurements were made using a Likert scale. This analytical method in this research is using a multiple linear regression. From this study, it was found that recruitment had an effect on employee productivity. Selection has no effect on employee productivity. The training has no effect on the employee’s work productivity PT SHF.